2016
DOI: 10.5897/ajfs2015.1412
|View full text |Cite
|
Sign up to set email alerts
|

Quality control of raw milk in the smallholder collection and bulking enterprises in Nakuru and Nyandarua Counties, Kenya

Abstract: Kenya has one of the largest dairy industries in sub-Saharan Africa. Most of the milk marketed by smallscale farmers in Kenya has been reported to be of poor quality and does not meet national and international standards due to high bacterial load, high somatic cell count, adulteration and antibiotic residues. This study was designed to assess status of microbiological and physico-chemical quality of raw milk from two smallholder dairy farmer' groups at four sampling levels. Three hundred and eight raw milk sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 4 publications
(5 reference statements)
1
3
1
Order By: Relevance
“…The consequences of antibiotic residues in milk are severe; for example, antibiotic residues can prevent optimum growth of starter cultures during processing of dairy products, and β-lactam antibiotics, if present, can cause allergic reactions in some individuals (Dewdney et al, 1991;Griffiths, 2019). Our results showed a markedly lower prevalence of antibiotic residues in farm bulk milk than has been reported by others: 44.5% reported in Kenya (Teresiah et al, 2016) in a study that used a kit similar to the one used here; 30% in Zambia (Kunda et al, 2016), using the Copan milk test (Copan Italia spa, Brescia, Italy); and 36% reported in Tanzania (Kurwijila et al, 2006), using the Charm AIM-96 (Charm Sciences Inc., Lawrence, MA) antimicrobial inhibition assay.…”
Section: Antibiotic Residues At the Farm And MCC Levelscontrasting
confidence: 54%
“…The consequences of antibiotic residues in milk are severe; for example, antibiotic residues can prevent optimum growth of starter cultures during processing of dairy products, and β-lactam antibiotics, if present, can cause allergic reactions in some individuals (Dewdney et al, 1991;Griffiths, 2019). Our results showed a markedly lower prevalence of antibiotic residues in farm bulk milk than has been reported by others: 44.5% reported in Kenya (Teresiah et al, 2016) in a study that used a kit similar to the one used here; 30% in Zambia (Kunda et al, 2016), using the Copan milk test (Copan Italia spa, Brescia, Italy); and 36% reported in Tanzania (Kurwijila et al, 2006), using the Charm AIM-96 (Charm Sciences Inc., Lawrence, MA) antimicrobial inhibition assay.…”
Section: Antibiotic Residues At the Farm And MCC Levelscontrasting
confidence: 54%
“…All farmers cooled milk using local methods, putting milk containers in cool water and very few had freezers. Our findings are also consistent with studies in Mali by [37] and in Kenya by [38], where most farmers, milk traders and bars held milk at ambient temperatures due to lack of cooling systems. Accordingly, milk cooling is not a common practice along the dairy chain, monitoring of milk safety and quality parameters is limited, particularly for pathogenic bacteria, indicating a risk for milk safety [9].…”
Section: A Milking Hygiene Milk Storage and Milk Safetysupporting
confidence: 91%
“…These antibiotics by means of antimicrobial deposits are present in profusion with in milk [13]. Occasionally these mixtures are correspondingly added to rise the shelf life of milk products [14]. The common antimicrobial medications are tetracyclines, sulphonamides, and nitrofurans antimicrobial remainder [15] in addition to some beta-lactam drugs like penicillin-G, amoxicillin, cloxacillin, dicloxacillin, cefuroxime and cefoperazone [16].…”
Section: The Antibiotics In Milkmentioning
confidence: 99%